AIDS and rural livelihoods: Dynamics and diversity in sub-Saharan Africa - Niehof, Anke; Rugalema, Gabriel; Gillespie, Stuart (Earthscan, 2010)
AIDS epidemics continue to threaten the livelihoods of millions of people in sub-Saharan Africa. Three decades after the disease was first recognized, the annual death toll from AIDS exceeds that from wars, famine and floods combined. Yet despite millions of dollars of aid and research, there has previously been little detailed on-the-ground analysis of the multifaceted impacts on rural people. Filling that gap, this book brings together recent evidence of AIDS impacts on rural households, livelihoods, and agricultural practice in sub-Saharan Africa. There is particular emphasis on the role of women in affected households, and on the situation of children. The book is unique in presenting micro-level information collected by original empirical research in a range of African countries, and showing how well-grounded conclusions on trends, impacts and local responses can be applied to the design of HIV-responsive policies and programmes. AIDS impacts are more diverse than we previously thought, and local responses more varied - sometimes innovative, sometimes desperate. The book represents a major contribution to our understanding of the impacts of AIDS in the epidemic's heartland, and how these can be managed at different levels.